Gambaran Tingkat Pengetahuan Tentang Pemeriksaan Sadari pada Wanita Usia Subur di RT 1 Desa Sungai Tabuk Kota - Yayang Elkagustia; Ika Friscila (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
A BSE examination is a self-examination of the breasts to find abnormal lumps. This examination can be done yourself without having to go to a health worker and without having to pay any money. The aim of the research was to determine the level of knowledge about BSE examinations in women aged Subir in RT 1 Sungai Tabuk Village, Kota. This type of quantitative research with a descriptive design uses one group pre test - post test design using the Cross Sectional method. The population is all women of childbearing age in RT 1 Sungai Tabuk Kota Village in the Working Area of Sungai Tabuk Kota 1 Community Health Center. The sample was taken using a total sampling technique, namely the entire sample of women of childbearing age in RT 1 Sungai Tabuk Kota Village was 15 people. The results of the pretest presentation of material regarding breast self-examination (BSE) to women of childbearing age showed that half of the respondents (53%) had insufficient knowledge. Meanwhile, the results of the posttest showed that there was a sufficient increase in respondents' knowledge (63%) and as many as (35%) respondents had good knowledge of breast self-examination (BSE) material.